Testing as an approach to control the Corona epidemic dynamics and avoid lockdowns - Thomas Gries; Paul J. J. Welfens (International Economics and Economic Policy, 2021)
Vaccinations, lockdowns and testing strategies are three potential elements of an effective anti-coronavirus, and in particular Covid-19, health policy. The following analysis considers - within a simple model - the potentially crucial role of a Corona testing approach in combination with a quarantine approach which is shown herein to be a substitute for broad lockdown measures. The cost of lockdowns/shutdowns are rather high so that – beyond progress in terms of a broad vaccination program – a rational testing strategy should also be carefully considered. Testing has to be organized on the basis of an adequate testing infrastructure which could largely be implemented in firms, schools, universities and public administration settings. As regards the cost of a systematic broad Covid-19 testing strategy, these could come close to 0.5% of national income if there are no vaccinations. The Testing & Quarantine approach suggested here – with tests for symptomatic as well as asymptomatic people - is based on a random sampling and would require rather broad and frequent testing; possibly one test per person every 7–10~days. At the same time, one should consider that the cost of further lockdowns/shutdowns of a duration of 1~month could be very high, such that a standard cost benefit analysis supports the testing approach suggested herein. Also, an optimal policy mix could be designed where both vaccinations and testing play a crucial role. As of late January 2021, no further lockdowns in Germany and other OECD countries would be necessary if a broad testing infrastructure can be established rather quickly. This in turn will reinforce economic optimism and help to jumpstart economic growth in Europe, the US and Asia in a solid way. The basic logic of the testing approach pointed out here for industrialized countries could also be applied in developing countries. The approach presented is complementary to the IMF analysis of Cherif/Hasanov.
Keywords: H12; H51; I10; I18; 330; Corona testing; Epidemic; Lockdowns; Cost pandemic response; World economy